2018
DOI: 10.1002/jcb.28313
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed circ_0029426 in glioblastoma forecasts unfavorable prognosis and promotes cell progression by sponging miR‐197

Abstract: Accumulating studies indicates that circular RNAs (circRNAs) play an imperative role in modulating cancer progression and metastasis. In the previous study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…miR-197 depletion exerts an tumor suppressive effect on the progression of gastric cancer [ 31 ]. Moreover, miR-197 has been shown to be suppressed cell proliferation, migration, and invasion in glioblastoma [ 32 ]. Hence, these studies demonstrated that miR-197 is involved in cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…miR-197 depletion exerts an tumor suppressive effect on the progression of gastric cancer [ 31 ]. Moreover, miR-197 has been shown to be suppressed cell proliferation, migration, and invasion in glioblastoma [ 32 ]. Hence, these studies demonstrated that miR-197 is involved in cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Many single studies have reported that dysregulated expression of circRNAs is a poor prognostic factor in glioma patients based on multivariate Cox regression analysis [13][14][15][16][17]33]. After a subgroup analysis, we found that circRNAs with different expression levels have different prognostic features in gliomas.…”
Section: Discussionmentioning
confidence: 69%
“…Circ_0029426 was upregulated in GBM tissues and this was associated with tumor size and World Health Organization grading (Zhang G. et al, 2019). Circ_0029426 was an independent prognostic factor for GBM and correlated with the poor OS (Zhang G. et al, 2019). It promotes GBM progression by sequestering miR-197 (Zhang G. et al, 2019).…”
Section: Glioblastoma (Gbm)mentioning
confidence: 95%
“…It sequesters miR-132 in GBM cells and its knockdown enhanced TMZ-sensitivity (Ding et al, 2020). Circ_0029426 was upregulated in GBM tissues and this was associated with tumor size and World Health Organization grading (Zhang G. et al, 2019). Circ_0029426 was an independent prognostic factor for GBM and correlated with the poor OS (Zhang G. et al, 2019).…”
Section: Glioblastoma (Gbm)mentioning
confidence: 95%
See 1 more Smart Citation